2018
DOI: 10.1002/er.4097
|View full text |Cite
|
Sign up to set email alerts
|

A solid oxide carbon fuel cell operating on pomelo peel char with high power output

Abstract: Summary The pomelo peel char (PC) was prepared and used as fuel for solid oxide electrolyte direct carbon fuel cells with nickel‐yttrium stabilized zirconia anode, thin‐film YSZ electrolyte, and La0.8Sr0.2MnO3 cathode. The power densities of fuel cells operating on PC and catalyst‐loaded PC (PCC) fuels achieved 309 and 518 mW cm−2 at 850°C, respectively, which are among the highest power densities reported in the literature on DCFCs. The PC exhibited superior gasification reactivity than coal char due to its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…By comparison DCFC has many advantages, particularly solid carbon is easy to transport, store and readily available from coal, coke, biomass and waste materials. DCFC has 100% theoretical efficiency, with more than 60% practical efficiency with low CO2 production [1][2][3][4]. In general, DCFCs directly transform chemical energy of carbon into electricity without any intermediate reformer, at higher efficiency than coal combustion power plants [5].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison DCFC has many advantages, particularly solid carbon is easy to transport, store and readily available from coal, coke, biomass and waste materials. DCFC has 100% theoretical efficiency, with more than 60% practical efficiency with low CO2 production [1][2][3][4]. In general, DCFCs directly transform chemical energy of carbon into electricity without any intermediate reformer, at higher efficiency than coal combustion power plants [5].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other fuel cells fed with gaseous fuel (such as H 2 , natural gas, CH 4 ), the exclusive characteristic of DC-SOFC is the solid fuel, which has a higher volumetric energy density. The solid fuel is convenient and safe to transport and can be obtained widely from coal [9][10][11][12][13][14][15] and biomass [3,16] (such as almond shells [17], wheat straw [18], corn cob char [19], pepper straw [20], and pomelo peel [21]). The concentration of solid fuel will not decrease due to the co-existence with gaseous products during the operation of the fuel cell, and thus the theoretical potential will not reduce.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this mechanism, the performance of DC-SOFC will be affected by the electrochemical oxidation of CO at TPBs in anodes, the Boudouard gasification and mass transport between anode and solid carbon fuel [25][26][27]. Besides development of new anode material and microstructure [19,[28][29][30], which can improve catalytical activity, mass transport, ionic or electronic conductivities of anode, plenty of experimental evidence demonstrates that carbon activity and transport properties in the anode can significantly influence the DC-SOFC performance [3,13,17,21,25,[31][32][33][34]. Liu et al [31] operated a tubular SOFC fed with the activated carbon and the results indicated that the fuel gas in the anode was insufficient and the mass transport in the anode was poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid oxide FCs also known as ceramic FCs are very efficient (almost 80% efficiency), fuel flexible, reliable, free from noise pollution, and have long life . They have greater conversion efficiency because they directly convert chemical energy to electrical energy, therefore, are seemed to be the promising alternatives energy source …”
Section: Introductionmentioning
confidence: 99%